Long-term trend in serum (1, 3)-β-D-glucan level in a man with chronic disseminated candidiasis treated with corticosteroids. Issue 8 (August 2021) - Shirahige, Tomoyuki; Tashiro, Masato; Taguchi, Masataka; Miyazaki, Yasushi; Shibuya, Kazutoshi; Izumikawa, Koichi
Abstract: Chronic disseminated candidiasis (CDC) is a type of invasive candidiasis. CDC commonly appears in the neutrophil recovery phase after chemotherapy in patients with hematologic malignancies, and immune reconstitution inflammatory syndrome (IRIS) is thought to play a major role in CDC development. This report describes the case of a 33-year-old man with CDC as a complication of acute myeloid leukemia. We describe the clinical course, body temperature, therapy, and (1, 3)-β-D-glucan (BDG) levels over the course of 22 months. He was initially treated with antifungals, but corticosteroids were added because of a persistently elevated body temperature, which we attributed to IRIS. After starting corticosteroids, his clinical condition improved, but his BDG levels became markedly elevated. We hypothesize that the suppression of the excessive immune response by corticosteroids lead to granuloma collapse, fungal release, and hematogenous dissemination, resulting in elevated BDG levels. The patient's condition gradually improved over the course of follow-up.